2018
DOI: 10.3389/fmicb.2018.02754
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects of High Fishmeal Diet on Gut Microbiota and Immune Response in Clostridium perfringens-Challenged Chickens

Abstract: Necrotic enteritis (NE) caused by Clostridium perfringens is responsible for huge financial losses in the poultry industry annually. A diet highly supplemented with fishmeal is one factor predisposing chickens to the development of clinical NE. However, the effects of fishmeal-rich diets on the gut microbiota and immune response in chickens with C. perfringens challenge over the long-term are not well-understood. Here, a chicken NE model was established in which chickens were fed high fishmeal diet and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…C. perfringens can disrupt the balance of chicken intestinal bacteria. For example, we observed that C. perfringens challenge decreases the abundance of the beneficial bacterium Lactobacillus salivarius , and this finding is consistent with those of previous studies (Lin et al, 2017; Huang et al, 2018). The results of the PCoA and species composition show that there are no significant differences between the intestinal microbiota structures in the CB/CP and CP groups, indicating that the beneficial effect of C. butyricum is less than the harmful effect of C. perfringens on the structure of the intestinal flora.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…C. perfringens can disrupt the balance of chicken intestinal bacteria. For example, we observed that C. perfringens challenge decreases the abundance of the beneficial bacterium Lactobacillus salivarius , and this finding is consistent with those of previous studies (Lin et al, 2017; Huang et al, 2018). The results of the PCoA and species composition show that there are no significant differences between the intestinal microbiota structures in the CB/CP and CP groups, indicating that the beneficial effect of C. butyricum is less than the harmful effect of C. perfringens on the structure of the intestinal flora.…”
Section: Discussionsupporting
confidence: 93%
“…The pathogenic C. perfringens cpnetBF carrying the netB gene was isolated from the intestines of broiler chickens with NE in Guangdong Province, China (Huang et al, 2018). The strain was stored at −80°C in fluid thioglycollate broth (FT, Beckson, Dickinson, and Company) supplemented with 30% glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the optimal choice of the hypervariable region(s) and primer combination vary between various ecological communities. Previous research proved that the highest bacterial diversity and species richness in chicken gut microbiomes were obtained using the primer set corresponding to the V3-V4 region 34,35 . Based on these investigations, in our study, we selected primers targeting the V3-V4 regions of the 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Clostridium sensu stricto 1 genus exhibited the highest abundance apart from the lactobacilli. This Clostridium genus has been shown to be associated with necrotic enteritis and Clostridium perfringens infection models [66,67]. However, the Clostridium sensu stricto 1 cluster also contains species such as C. butyricum, which has also been used as a probiotic in poultry [68].…”
Section: Discussionmentioning
confidence: 99%